1965
DOI: 10.1042/bj0960098
|View full text |Cite
|
Sign up to set email alerts
|

Carp Myogens of White and Red Muscles. Properties and Amino Acid Composition of the Main Low-Molecular-Weight Components of White Muscle

Abstract: 1. The three main components of the 1.5-2s ultracentrifugal peak of carp myogen (white muscle) have been isolated by ammonium sulphate fractionation and zone electrophoresis, and crystallized. 2. The molecular weights of these three proteins were determined by sedimentation and diffusion, by the Archibald method and by amino acid analysis, and found to lie between 9000 and 13000. 3. Their complete amino acid compositions were determined by column chromatography and by their ultraviolet spectra. Both methods re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
25
0

Year Published

1972
1972
2008
2008

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 15 publications
4
25
0
Order By: Relevance
“…Because of the lack of tyrosine and tryptophan and because of the low extinction coefficient for phenylalanine, the denaturation reaction of band 5 could not be suitably monitored by UV absorption as has been done with other proteins. We unsuccessfully tried several other methods before finally settling on phenylalanine fluorescence for detection.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Because of the lack of tyrosine and tryptophan and because of the low extinction coefficient for phenylalanine, the denaturation reaction of band 5 could not be suitably monitored by UV absorption as has been done with other proteins. We unsuccessfully tried several other methods before finally settling on phenylalanine fluorescence for detection.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…In view of this property, this protein has been designated carp-muscle calcium-binding protein. These proteins apparently are not involved in glycolysis or osmotic regulation, nor do they serve any known nutritional role (2,3). However, several features suggest that they are related to mammalian troponin A (4).…”
mentioning
confidence: 99%
“…They are defined by the following characteristics: (a) high solubility in water, (b) precipitation between 70-and 95%-saturated ammonium sulfate, (c) unusual amino-acid compositions, with 10% phenylalanine, 20% alanine, and only one or no tryptophan, tyrosine, arginine, histidine, cysteine, proline, or methionine residues, (d) isoelectric points between pH 4.0 and 4.5, and (e) molecular weights about 12,000 (1)(2)(3). Pechere (4) has shown that one of the hake parvalbumins binds calcium, as does the carp protein described here.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The parvalbumins are low molecular weight, acidic, watersoluble, calcium-binding proteins long believed to occur exclusively in the white muscle of lower vertebrates and for which no physiological function has been determined as yet (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Amino-acid sequences indicate that they are homologous (10,12,13) and that this homology extends to other muscle calcium-binding proteins, such as troponin C and one of the light chains of myosin (14).…”
mentioning
confidence: 99%